1989
DOI: 10.1083/jcb.109.2.487
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted yeast mitochondria can import precursor proteins directly through their inner membrane.

Abstract: Abstract. Import of precursor proteins into the yeast mitochondrial matrix can occur directly across the inner membrane. First, disruption of the outer membrane restores protein import to mitochondria whose normal import sites have been blocked by an antibody against the outer membrane or by a chimeric, incompletely translocated precursor protein. Second, a potential-and ATP-dependent import of authentic or artificial precursor proteins is observed with purified inner membrane vesicles virtually free of outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 25 publications
3
62
0
Order By: Relevance
“…Evidence that the nuclease protection of tRNA represents importation into the mitochondrion: Cleavage of a heterologous precursor tRNA by an intramitochondrial RNase P-like activity Pre-tRNA Asp from Bacillus subtilis is a precursor tRNA that is cleaved by RNase P into the mature tRNA and a 59 leader+ We found that incubation of T7-transcribed pre-tRNA Asp with L. tarentolae mitochondria in the presence of ATP produced a cleavage of the precursor into a species that comigrated with the mature tRNA and that was protected from nuclease digestion (Fig+ 4A)+ Another fragment appeared even at low ATP levels that comigrated with the 33-nt 59 leader, but as this fragment also appeared with 39 end-labeled pre-tRNA These data indicate that the nuclease protection of RNA represents importation into the matrix of the organelle, because there is processing of the pre-tRNA into a mature tRNA that is carried out by an RNase P-like cleavage activity localized within the mitochondrial matrix+ A similar activity was previously detected in mitochondria from Trypanosoma brucei (Hancock et al+, 1992)+ Additional evidence that the nuclease protection of tRNA represents importation into the mitochondrion: Titration with digitonin Digitonin selectively solubilizes the outer mitochondrial membrane at low concentrations due to the high levels of cholesterol in that membrane (Schnaitman & Greenawalt, 1968)+ RNAs attached to the outer mitochondrial membrane or the outer side of the inner mitochondrial membrane should be nuclease sensitive at low digitonin concentrations that should only break down the outer membrane+ However, RNAs within the matrix should become nuclease sensitive at higher digitonin concentrations that also break down the inner membrane+ To provide a matrix marker, endogenous matrix-localized tRNAs were 39-end labeled with [a-32 P]CTP by an intramitochondrial ATP(CTP) nucleotidyltransferase activity previously shown to exist in T. brucei mitochondria (Hancock et al+, 1992)+ In a parallel experiment, mitochondria were incubated with uniformly labeled tRNA Ile in the presence of ATP+ The nuclease protection of the tRNA Ile at increasing digitonin concentrations was compared to that of the labeled endogenous mitochondrial tRNAs+ As shown in Figure 6, the latency of the tRNA Ile with digitonin was identical within experimental error to that of the labeled endogenous tRNAs+ This suggests that the tRNA Ile was imported into the mitochondrial matrix and not sequestered on the surface in a nucleaseresistant manner+ This method of digitonin solubilization has been used previously to show that tagged tRNAs transcribed from plasmids in vivo are targeted to the mitochondrial matrix (Lima & Simpson, 1996)+ Lack of requirement for a membrane potential L. tarentolae mitochondria isolated in Percoll gradients after hypotonic (Fig+ 7A) or isotonic (Fig+ 7B) cell breakage have measurable membrane potentials, as determined using the potential-sensitive fluorescent dye, diS-C 3 -(5) (Sims et al+, 1974;Hwang et al+, 1989;Hauser et al+, 1996)+ Furthermore, freezing the mitochondria at Gln (squares)+ B: Labeled tRNA Gln (3 pmol, 2+4 ϫ 10 4 cpm) was incubated with mitochondria in the presence of increasing amounts of unlabeled tRNA Ile (circles) or tRNA Gln (squares)+ The extent of nuclease protection was analyzed as described in Materials and methods+ Ϫ80 8C in glycerol had little effect on either the membrane potential or the nuclease p...…”
Section: In Vitro-transcribed Trnamentioning
confidence: 99%
“…Evidence that the nuclease protection of tRNA represents importation into the mitochondrion: Cleavage of a heterologous precursor tRNA by an intramitochondrial RNase P-like activity Pre-tRNA Asp from Bacillus subtilis is a precursor tRNA that is cleaved by RNase P into the mature tRNA and a 59 leader+ We found that incubation of T7-transcribed pre-tRNA Asp with L. tarentolae mitochondria in the presence of ATP produced a cleavage of the precursor into a species that comigrated with the mature tRNA and that was protected from nuclease digestion (Fig+ 4A)+ Another fragment appeared even at low ATP levels that comigrated with the 33-nt 59 leader, but as this fragment also appeared with 39 end-labeled pre-tRNA These data indicate that the nuclease protection of RNA represents importation into the matrix of the organelle, because there is processing of the pre-tRNA into a mature tRNA that is carried out by an RNase P-like cleavage activity localized within the mitochondrial matrix+ A similar activity was previously detected in mitochondria from Trypanosoma brucei (Hancock et al+, 1992)+ Additional evidence that the nuclease protection of tRNA represents importation into the mitochondrion: Titration with digitonin Digitonin selectively solubilizes the outer mitochondrial membrane at low concentrations due to the high levels of cholesterol in that membrane (Schnaitman & Greenawalt, 1968)+ RNAs attached to the outer mitochondrial membrane or the outer side of the inner mitochondrial membrane should be nuclease sensitive at low digitonin concentrations that should only break down the outer membrane+ However, RNAs within the matrix should become nuclease sensitive at higher digitonin concentrations that also break down the inner membrane+ To provide a matrix marker, endogenous matrix-localized tRNAs were 39-end labeled with [a-32 P]CTP by an intramitochondrial ATP(CTP) nucleotidyltransferase activity previously shown to exist in T. brucei mitochondria (Hancock et al+, 1992)+ In a parallel experiment, mitochondria were incubated with uniformly labeled tRNA Ile in the presence of ATP+ The nuclease protection of the tRNA Ile at increasing digitonin concentrations was compared to that of the labeled endogenous mitochondrial tRNAs+ As shown in Figure 6, the latency of the tRNA Ile with digitonin was identical within experimental error to that of the labeled endogenous tRNAs+ This suggests that the tRNA Ile was imported into the mitochondrial matrix and not sequestered on the surface in a nucleaseresistant manner+ This method of digitonin solubilization has been used previously to show that tagged tRNAs transcribed from plasmids in vivo are targeted to the mitochondrial matrix (Lima & Simpson, 1996)+ Lack of requirement for a membrane potential L. tarentolae mitochondria isolated in Percoll gradients after hypotonic (Fig+ 7A) or isotonic (Fig+ 7B) cell breakage have measurable membrane potentials, as determined using the potential-sensitive fluorescent dye, diS-C 3 -(5) (Sims et al+, 1974;Hwang et al+, 1989;Hauser et al+, 1996)+ Furthermore, freezing the mitochondria at Gln (squares)+ B: Labeled tRNA Gln (3 pmol, 2+4 ϫ 10 4 cpm) was incubated with mitochondria in the presence of increasing amounts of unlabeled tRNA Ile (circles) or tRNA Gln (squares)+ The extent of nuclease protection was analyzed as described in Materials and methods+ Ϫ80 8C in glycerol had little effect on either the membrane potential or the nuclease p...…”
Section: In Vitro-transcribed Trnamentioning
confidence: 99%
“…However, import of some precursor proteins could be restored if the outer membrane of these mitochondria was opened (Hwang et al, 1989). In the second case, inner membrane vesicles virtually free of outer membrane components were shown to import several mitochondrial precursor proteins in an ATP-and membrane potential-dependent manner (Hwang et al, 1989). These data support the view that the inner membrane contains an import machinery which in principle can act independently of that in the outer membrane.…”
Section: The Transport Machineries Of the Inner And Outer Membrane Armentioning
confidence: 53%
“…This treatment led to an import inhibition of other precursor proteins (Vestweber & Schatz, 1988;Rassow et al, 1989). However, import of some precursor proteins could be restored if the outer membrane of these mitochondria was opened (Hwang et al, 1989). In the second case, inner membrane vesicles virtually free of outer membrane components were shown to import several mitochondrial precursor proteins in an ATP-and membrane potential-dependent manner (Hwang et al, 1989).…”
Section: The Transport Machineries Of the Inner And Outer Membrane Armentioning
confidence: 99%
“…(The energetics of translocation into the matrix are discussed in detail in the next section). 256 It has also been found that mitoplasts, i.e., mitochondria in which the OM has been disrupted and partly removed, the import of various preproteins can take place [33]. This supports the view that also the IM translocation system on its own can translocate proteins.…”
Section: Transport Of Proteins Across Both Outer and Inner Membranesmentioning
confidence: 66%